New learning spaces and transformations in teacher pedagogy and student learning behavior in the language learning classroom - Radha M K Nambiar,; Noorizah Mohd Nor,; Kemboja Ismail,; Shahirah Adam, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Many Malaysian classrooms have been redesigned to include technology and foster the development of twenty first century learning. The availability of this platform and the new learning space created by redesigning the language classroom has opened up new and exciting possibilities for teaching and learning the English language. This paper will investigate if the new learning space has impacted teacher’s pedagogical strategies and student’s learning behavior and engagement for English language teaching and learning. A qualitative approach employing a multiple case study research design was taken and data was collected using classroom observations, teacher interviews and teacher and student focus group discussions from eight English language teachers and 37 students. Findings reveal significant transformations in teachers’ teaching approaches, use of class activities and on students’ learning behavior and outcomes. Technology did feature in the learner centric approach with students functioning as facilitators and allowing more student participation and interaction. The use of multimedia and online materials helped make learning more interesting and improved student attention in class. Students in turn were more focused and engaged in the collaborative tasks and also reported developing better peer relationships and learning from each other.